Sosialitas dalam Perspektif Filsafat Sosial - Siswanto, Dwi (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2004)
The human sociality is one element that makes man different with other creature; so that the sociality is the man nature.The human sociality process a great dimension. Man was called human being as far as build a relation with other. Man is impossible to live alone. Proverb said'